Analyse the Impact of Ecotourism on Animal Biodiversity: Impacts of Ecotourism on Animal Biodiversity: A Case Study of Brownsberg (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Ecotourism has been linked to a decline in biodiversity, with some studies suggesting it can impact species occurrence, survival, or behavior. However, others argue that ecotourism acts as a human shield to deter negative practices like gold mining, logging, and hunting. Brownsberg. Most species avoid areas with many hikers or switch to nocturnal activity patterns, causing a significant decrease in the diversity of mammals. Vehicles have little impact on species avoidance or diversity but increase nocturnality more than hikers. Some species, like giant armadillos and spotted pacas, seem to be attracted by hikers and traffic, while others, like ocelots, margays, and red-rumped agoutis, favor human disturbance due to predator release. The most impacted species are jaguar, puma, and lowland tapir, all of which contribute significantly to ecosystem balance. Management measures should focus on reducing hikers in popular areas and limiting vehicle use in recreational areas.